Abscisic acid and hydrogen peroxide are involved in drought priming‐induced drought tolerance in wheat (Triticum aestivum L.). (9th September 2020) - Wang, X.; Zhang, J.; Song, J.; Huang, M.; Cai, J.; Zhou, Q.; Dai, T.; Jiang, D.
Abstract: Drought is one of the major stress factors in wheat production on a global scale. Drought priming during the early growth stage can enhance drought tolerance in wheat ( Triticum aestivum L.). Abscisic acid (ABA) and hydrogen peroxide (H2 O2 ) are important signal molecules in the adaptation of plants to drought stress. However, the roles of ABA and H2 O2 in drought priming‐induced drought tolerance are not clear. In the present study, we evaluated the responses of wheat to an ABA inhibitor, H2 O2 scavenger and an inhibitor to investigate the (i) relationship between ABA and H2 O2 in osmotic adjustment after drought priming in the vegetative stage and (ii) responses to drought stress during grain filling. In the drought priming alone treatments, chemical application resulted in the scavenging of ABA and H2 O2, weakening the alleviation effects of drought priming on drought stress, as demonstrated by the lower leaf water potential and grain yield. The ABA inhibitor completely inhibited accumulation of ABA and H2 O2 ; the ABA inhibitor inhibited respiratory burst oxidase homologue expression, whereas the H2 O2 inhibitor resulted in higher 9‐cis‐epoxycarotenoid dioxygenase expression and ABA concentration in primed plants, indicating that ABA scavenging inhibited H2 O2 biosynthesis while H2 O2 scavenging did not inhibit ABA biosynthesis. The results further demonstrated that NADPH oxidase‐mediated H2 O2 production functions downstream of ABA, which induces osmolyte transcript expression and accumulation, and thus contributes to drought priming‐induced stress tolerance. These results provide a theoretical basis for a better understanding of the mechanisms involved in drought priming‐induced tolerance in wheat plants. Abstract : The NADPH oxidases‐mediated H2 O2 production works in downstream of ABA induced osmolyte accumulation, which contributes to drought priming induced stress tolerance in wheat.